Sikap Pemustaka Terhadap Layanan Sirkulasi di Perpustakaan Proklamator Bung Hatta Bukittinggi - Hidayat, Taufik; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
Based on the results of the analysis of these data, it can be drawn a conclusion that user attitude towards services provided in library circulation Bung Hatta Bukittinggi, in terms of attitudes towards service consumer of library member registration, loans, returns, billing, as well as sanctions against the delay user the return of library materials that have exceeded the time limit borrowing, the average pemustaka agree with the system of services provided by the library staff Bung Hatta Bukittinggi. Because with the services provided are not burdensome and difficult for any used who came to the service at the library circulation Bung Hatta Bukittinggi. Judging from the attitude towards statistics library that is not on display at the library, user not agree with that. As for the statistics of Bung Hatta Library Bukittinggi, does not meet the standard of a library. The work done by librarians for library circulation service at Bung Hatta Bukittinggi in improving circulation service is to improve the performance of such services librarian at the library membership registration maid service, borrow and return library materials. Keywords: library circulation; users attitude